Hegemoni dan Resistensi dalam Kasus Pelecehan Seksual: Analisis Simbol dalam Film Penyalin Cahaya - Utami, Puspa Indah; Sari, Artanti Puspita; Indrawati, Sri Wahyu; Fitriani, Yessi (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
The purpose of this research was to gain a deep understanding of analyzing the hegemony of power and resistance of the Indonesian film entitled Penyalin Cahaya. This study uses a qualitative descriptive research method used to analyze the hegemony and resistance as well as the symbols contained in the film Copying Light. Data collection uses literature study, observation, and documentation techniques. The steps used in analyzing films with the theme of sexual harassment are: 1) watching and observing carefully repeatedly every scene and dialogue in the film, 2) classifying data by capturing the scenes of each scene in the film, 3) , analyzing, reading, and recording every scene and dialogue that is considered important, 4) analyzing symbols, 5) analyzing the hegemony and resistance contained in the film Copying Light, 6) making conclusions from the analysis carried out, and 7) compiling a research report. The results of the study show that the behavior experienced by victims of sexual crimes in the film Copying Light is inseparable from the hegemony of power and victims are forced to remain silent from the sexual harassment they experience.